ANGIOGRAPHIC PREVALENCE OF MYOCARDIAL MUSCLE BRIDGING IN PATIENTS WITH CHEST PAI - Rana, Faraz Saeed; Shehzad, Syed Khurram; Akhtar, Muhaamad Shoaib; Usman, Maria; Daniyal, Shoaib Muhammad; Ahmad, Ayaz (Pakistan Armed Forces Medical Journal, 2019)
Objective: To determine the angiographic prevalence of myocardial bridging in patients with chest pain. Study Design: Prospective observational study. Place and Duration of Study: Army Cardiac Center, Lahore over a period of seven years, from Jan 2011 to Dec 2017. Methodolgy: In this prospective observational study, we evaluated the findings of coronary angiograms of patients who presented with chest pain during the period of seven years (2011-2017). The number of patients with myocardial bridge were identified. The location of Muscle Bridge and percentage of systolic squeeze was noted down. Results: Of 15,007 patients, 45 patients (0.29%) were found to have myocardial muscle bridge. Forty four (97.8%) of these patients had Left Anterior Descending (LAD) Artery involved. 53.3% of the patients had more than 50% systolic squeeze. Conclusion: The prevalence of MB in our setting is low in angiographic study. LAD is the most common intramural artery.